Low-cost oxide-chloride composite solid electrolyte material and preparation method and application thereof

By introducing oxide-chloride composite solid electrolyte materials into Li2ZrCl6 electrolyte, uniform dispersion and doping of metal oxide particles is achieved by using the ball milling method, the problems of high cost and low conductivity of existing electrolytes are solved, and the lithium ion conductivity and battery performance are significantly improved.

CN119764539APending Publication Date: 2025-04-04HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510126823.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing cationic or anion-doped modified Li2ZrCl6 electrolytes are costly and have low room temperature lithium ion conductivity, which limits the power density of the battery.

Method used

A low-cost oxide-chloride composite solid electrolyte material is used, with the chemical formula of xMOm/2-Li2ZrCl6. The metal oxide and Li2ZrCl6 electrolyte are mixed by ball milling to achieve uniform dispersion of metal oxide particles in the composite electrolyte and double doping of the anion (O2-) and cation (Mm+) of the Li2ZrCl6 electrolyte.

Benefits of technology

The lithium ion conductivity of the composite electrolyte is significantly improved to reach 2.01×10-3S cm-1, reducing the cost of raw materials and improving the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764539A_ABST
    Figure CN119764539A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost oxide-chloride composite solid electrolyte material as well as a preparation method and application thereof, relates to an oxide-chloride composite solid electrolyte material as well as a preparation method and application thereof, and aims to solve the technical problem of high cost of the conventional cation or anion doped modified Li2ZrCl6 electrolyte. The chemical formula of the composite solid electrolyte material is xMOm / 2-Li2ZrCl6, 0lt, xlt; m is one or more of Al, Fe, La, Ce, Sm, Nd, Ti, Zn, Cu, Mg, Zr, Cr, Mn, V, Ca and Sn. In the composite electrolyte prepared by using a ball milling method, metal oxide particles are uniformly dispersed, and the Li2ZrCl6 electrolyte is subjected to anion O2-and cation Mm + double doping, so that the lithium ion conductivity is improved. And the prepared all-solid-state lithium battery has no capacity attenuation after being charged and discharged for 50 cycles at 0.5 C multiplying power, and can be applied to all-solid-state lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an oxide-chloride composite solid electrolyte material and a preparation method and application thereof, belonging to the technical field of lithium batteries. Background Art

[0002] In recent years, people's growing demand for energy is accelerating the exploration of high-energy density electrode materials, while the specific energy of traditional lithium-ion batteries has reached its upper limit and is difficult to break through in a short period of time. In addition, lithium-ion battery systems using organic solvents as electrolytes have safety hazards such as fire and explosion. The use of all-solid-state electrolytes to replace organic electrolytes as lithium battery electrolytes has attracted widespread attention due to their excellent mechanical strength and chemical stability, and has become one of the potential paths for the future development of lithium-ion batteries.

[0003] Halide solid electrolyte (Li a RCl b , R is a metal element) as an inorganic all-solid-state electrolyte, has the advantages of good oxygen resistance, high oxidation stability, high deformability, and can match 4V-level high-voltage positive electrode materials without coating layers, and has become an optional strategy for the practical application of solid electrolytes. At present, there are still many problems with halide-based solid electrolytes, which limits their further large-scale application. Halide solid electrolytes usually use anhydrous metal halides as raw materials. In addition to the commonly used LiCl, they also require anhydrous scandium chloride (ScCl3), anhydrous yttrium chloride (YCl3), anhydrous indium chloride (InCl3), etc. These elements are often expensive and have low reserves in the earth's crust. This greatly increases its preparation cost and cannot meet the growing demand for energy storage devices. In addition, the room temperature lithium ion conductivity of most halide solid electrolytes is still low (~10 -4 Scm -1 ), and has not yet met the general requirements for solid electrolyte ion conductivity (>10 -3 S cm -1 ). Recently, a Li2ZrCl6 electrolyte prepared by ball milling using Zr, an element with high abundance in the earth's crust, as the metal element R was reported. This electrolyte has a low raw material cost and has a certain promotion value. However, the room temperature ionic conductivity of this electrolyte is only 4×10 -4 S cm -1 , low lithium ion conductivity may lead to severe polarization during charge and discharge, limiting the power density of the battery. Studies have shown that doping this electrolyte with cations or anions may increase its conductivity to 10 -3 Scm -1However, these strategies are often accompanied by a significant increase in cost. Therefore, developing a cost - effective strategy for modifying Li2ZrCl6 electrolytes while enhancing their ionic conductivity is of great value for both basic research and commercial promotion in the field of halide solid electrolytes. Summary of the Invention

[0004] The present invention aims to solve the technical problem of the high cost of existing cation - or anion - doped modified Li2ZrCl6 electrolytes, and provides a low - cost oxide - chloride composite solid electrolyte material, its preparation method and application, so as to provide a strategy with both cost advantages and performance advantages for the popularization of chloride solid electrolytes.

[0005] The chemical formula of the low - cost oxide - chloride composite solid electrolyte material of the present invention is xMO m / 2 -Li2ZrCl6, where 0 < x < 2, M is the metal element in the oxide, and m is the valence of the metal element M; M is one or more of the elements of aluminum (Al), iron (Fe), lanthanum (La), cerium (Ce), samarium (Sm), neodymium (Nd), titanium (Ti), zinc (Zn), copper (Cu), magnesium (Mg), zirconium (Zr), chromium (Cr), manganese (Mn), vanadium (V), calcium (Ca) and tin (Sn).

[0006] The oxide - chloride composite solid electrolyte material of the present invention is a two - phase Li2ZrCl6 electrolyte co - doped with metal oxide - anions (O 2- ), cations (M m+ ), and has a high lithium - ion conductivity. When 0 < x < 0.2, the metal oxide with a low concentration cannot enter the interior of the Li2ZrCl6 lattice, and the composite electrolyte material exists in the form of metal oxide and Li2ZrCl6 two - phases; when 0.2 ≤ x ≤ 0.75, the metal oxide enters the interior of the Li2ZrCl6 lattice, and some excessive metal oxide particles still exist as independent phases in the composite electrolyte, forming a two - phase composite electrolyte structure in which the metal oxide is uniformly dispersed in the anion (O 2- ), cation (M m+ ) co - doped Li2ZrCl6 electrolyte. The lithium - ion transport rate at the interface between the metal oxide - co - doped Li2ZrCl6 electrolyte is greater than that of any one of the two phases, realizing the improvement of the ionic conductivity of the composite electrolyte; when 0.75 ≤ x < 2, the composite electrolyte still exists in the above - mentioned two - phase form, and a large number of excessive metal oxide particles exist in an aggregated form, increasing the interfacial ionic resistance.

[0007] The preparation method of the above - mentioned low - cost oxide - chloride composite solid electrolyte material is carried out according to the following steps:

[0008] I. According to the stoichiometric ratio of xMO m / 2 -Li2ZrCl6, mix the raw materials LiCl, ZrCl4 and MO m / 2 uniformly to obtain a mixed powder; where in xMO m / 2 -Li2ZrCl6, 0 < x < 2, M is the metal element in the oxide, and m is the valence of the metal element M; M is one or more of Al, Fe, La, Ce, Sm, Nd, Ti, Zn, Cu, Mg, Zr, Cr, Mn, V, Ca and Sn;

[0009] II. Ball mill the mixed powder described in Step I for 16 - 500 h under the conditions that the ball-to-material mass ratio is (5 - 40):(1 - 2) and the ball mill rotation speed is 400 - 700 rpm to obtain a low-cost oxide-chloride composite solid electrolyte material.

[0010] Furthermore, the ball milling process described in Step II is completed under the protection of an inert gas.

[0011] Furthermore, the ball milling process described in Step II is completed in an argon (Ar) environment with a water content and an oxygen content of < 0.01 ppm.

[0012] The application of the above low-cost oxide-chloride composite solid electrolyte material is to use this low-cost oxide-chloride composite solid electrolyte material as a lithium-ion battery electrolyte material. The composite solid electrolyte provided by the present invention has a high ionic conductivity at room temperature.

[0013] The application of the above low-cost oxide-chloride composite solid electrolyte material is to use the low-cost oxide-chloride composite solid electrolyte material in all-solid-state lithium batteries.

[0014] An all-solid-state lithium battery, the solid electrolyte of this battery uses a low-cost oxide-chloride composite solid electrolyte material as the main electrolyte; its positive electrode is composed of an active material, a low-cost oxide-chloride composite solid electrolyte material and a conductive agent mixed in a mass ratio of (60 - 70):(20 - 30):(0 - 20); where the active material is lithium cobaltate and / or nickel cobalt manganese ternary lithium positive electrode material; the conductive agent is a combination of one or several of carbon nanotubes (CNTs), vapor-grown carbon fibers (VGCF) and super carbon black (Super P);

[0015] Furthermore, the interlayer electrolyte of the all-solid-state lithium battery is Li3PS4, Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Cl、Li 10 GeP2S 12 and Li7P3S11 One or a combination of several of them;

[0016] Furthermore, the negative electrode of the all-solid-state lithium battery is a lithium-indium (Li-In) alloy.

[0017] Furthermore, the mass ratio of the main electrolyte to the separator electrolyte of the all-solid-state lithium battery is (1-10):3.

[0018] In the oxide-chloride composite solid electrolyte material with low raw material cost provided by the present invention, the metal oxide and the Li2ZrCl6 electrolyte are mixed by ball milling, so as to achieve uniform dispersion of the metal oxide particles in the composite electrolyte and the anion (O 2- ), cation (M m+ ) dual doping to achieve the goal of improving the lithium ion conductivity of Li2ZrCl6 electrolyte.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) In the oxide-chloride composite solid electrolyte material with low raw material cost provided by the present invention, low-cost metal oxides are used to replace expensive anhydrous metal chlorides as modified raw materials for Li2ZrCl6, so it has obvious cost advantages. Compared with anhydrous metal chlorides, metal oxides are generally easier to prepare and store, which is suitable for industrial-scale production. For example, Fe2O3 can be directly purified from hematite, or directly sintered from ferrous sulfate, a by-product of titanium dioxide industry, while anhydrous FeCl3 needs to be obtained through a complex process of FeCl3·6H2O in a hydrochloric acid (HCl) atmosphere, which may cause additional energy consumption and environmental pollution.

[0021] (2) The present invention provides an oxide-chloride composite solid electrolyte material with low raw material cost, wherein Li2ZrCl6 electrolyte and MO m / 2 By controlling the ratio of Li2ZrCl6 electrolyte to metal oxide, the uniform dispersion of metal oxide particles in the composite electrolyte and the anion (O 2- ), cation (M m+ ) double doping, increasing the Li + The transfer rate of the composite electrolyte is improved, and the lithium ion conductivity of the composite electrolyte is improved. The results of the embodiment show that the lithium ion conductivity of the oxide-chloride composite solid electrolyte material obtained by the present invention can reach 2.01×10 -3 S cm -1 .

[0022] (3) The method for preparing the oxide-chloride composite solid electrolyte material with low raw material cost provided by the present invention adopts a simple one-step ball milling synthesis process and can be prepared without annealing or multiple raw material collections, and is suitable for industrial large-scale production.

[0023] (4) The present invention provides an all-solid-state lithium battery. The above-mentioned oxide-chloride composite solid electrolyte has good compatibility with the 4V positive electrode, improves the interface contact between the positive electrode and the electrolyte, and improves the electrochemical performance of the all-solid-state lithium battery. The results of the embodiment show that the capacity retention rate of the full battery assembled with the oxide-chloride composite solid electrolyte material obtained by the present invention as the main electrolyte is 100% during the first 50 charge and discharge cycles at a rate of 0.5C, without obvious attenuation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The AC impedance spectrum corresponding to the ionic conductivity test of Comparative Example 1;

[0025] Figure 2 The AC impedance spectra corresponding to the ionic conductivity tests of Examples 1 to 3;

[0026] Figure 3 The AC impedance spectra corresponding to the ionic conductivity tests of Examples 4 to 8;

[0027] Figure 4 The AC impedance spectrum corresponding to the ionic conductivity test of Example 9;

[0028] Figure 5 It is the XRD spectrum of comparative example 1;

[0029] Figure 6 It is the XRD spectra of Example 6 and Example 7;

[0030] Figure 7 1 is a schematic structural diagram of the all-solid-state lithium battery described in Example 10, in which 1 is a Li-In alloy negative electrode, 2 is a separator electrolyte, 3 is an oxide-chloride composite solid electrolyte, 4 is a composite positive electrode, 5 is a cylindrical PEEK mold, 6 is a negative electrode current collector, and 7 is a positive electrode current collector;

[0031] Figure 8 The coulombic efficiency-capacity diagram of the constant current-constant voltage charge / constant current discharge test of the all-solid-state lithium battery prepared in Example 10;

[0032] Fig. 9 The charge and discharge curve diagram of the first cycle activation process of the all-solid-state lithium battery prepared in Example 10;

[0033] Fig.10 The charge and discharge curve diagram of the first charge and discharge cycle of the all-solid-state lithium battery prepared in Example 10;

[0034] Fig.11 The charge and discharge curve diagram of the second charge and discharge cycle of the all-solid-state lithium battery prepared in Example 10;

[0035] Fig.12 The charge and discharge curve diagram of the 20th charge and discharge cycle of the all-solid-state lithium battery prepared in Example 10;

[0036] Fig.13 This is a charge and discharge curve diagram of the 50th charge and discharge cycle of the all-solid-state lithium battery prepared in Example 10. DETAILED DESCRIPTION

[0037] The oxide-chloride composite solid electrolyte material with low raw material cost of the present invention and its preparation method and application are described below in combination with Comparative Example 1 and Examples 1-10. The materials provided in the Examples and Comparative Examples of the present invention are all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0038] Comparative Example 1: In this comparative example, there is no mixing with metal oxides, and the chloride solid electrolyte is directly prepared by ball milling. The specific preparation method is as follows: In a glove box, weigh 0.4000g LiCl (anhydrous, purity 99.9%) and 1.100g ZrCl4 (anhydrous, purity 99%) respectively, mix them evenly, add the mixture into a ball mill made of zirconium oxide (ZrO2) and seal it. Among them, the ball-to-material mass ratio is 35:1.5, and the ball mill is placed in a planetary ball mill and ball milled at 600rpm for 40h to obtain the electrolyte described in Comparative Example 1, whose chemical formula is Li2ZrCl6.

[0039] Example 1: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0040] 1. In a glove box, weigh 0.3759 g LiCl (anhydrous, purity 99.9%), 1.034 g ZrCl4 (anhydrous, purity 99%) and 0.0904 g Al2O3 (purity 99.99%) respectively and mix them evenly to obtain a mixed powder;

[0041] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the ball-to-material mass ratio is 35:1.5, place the ball mill in a planetary ball mill and ball mill it at 600 rpm for 160 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.2Al2O3-Li2ZrCl6.

[0042] Example 2: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0043] 1. In a glove box, weigh 0.3614 g LiCl (anhydrous, purity 99.9%), 0.9938 g ZrCl4 (anhydrous, purity 99%) and 0.1447 g Al2O3 (purity 99.99%) respectively, and mix them evenly to obtain a mixed powder;

[0044] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the ball-to-material mass ratio is 35:1.5, and place the ball mill in a planetary ball mill and ball mill it at 600 rpm for 160 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.33Al2O3-Li2ZrCl6.

[0045] Example 3: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0046] 1. In a glove box, weigh 0.3447 g LiCl (anhydrous, purity 99.9%), 0.9480 g ZrCl4 (anhydrous, purity 99%) and 0.2073 g Al2O3 (purity 99.99%) respectively, and mix them evenly to obtain a mixed powder;

[0047] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the ball-to-material mass ratio is 35:1.5, place the ball mill in a planetary ball mill and ball mill at 600 rpm for 40 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.5Al2O3-Li2ZrCl6.

[0048] Example 4: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0049] 1. In a glove box, weigh 0.3635 g LiCl (anhydrous, purity 99.9%), 0.9996 g ZrCl4 (anhydrous, purity 99%) and 0.1369 g Fe2O3 (purity 99.9%) respectively, and mix them evenly to obtain a mixed powder;

[0050] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the ball-to-material mass ratio is 35:1.5, and place the ball mill in a planetary ball mill and ball mill it at 600 rpm for 80 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.2Fe2O3-Li2ZrCl6.

[0051] Example 5: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0052] 1. In a glove box, weigh 0.3427 g LiCl (anhydrous, purity 99.9%), 0.9423 g ZrCl4 (anhydrous, purity 99%) and 0.2149 g Fe2O3 (purity 99.9%) respectively, and mix them evenly to obtain a mixed powder;

[0053] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the mass ratio of the ball to the material is 35:1.5, and place the ball mill in a planetary ball mill and ball mill it at 600 rpm for 80 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.33Fe2O3-Li2ZrCl6.

[0054] Example 6: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0055] 1. In a glove box, weigh 0.3197 g LiCl (anhydrous, purity 99.9%), 0.8792 g ZrCl4 (anhydrous, purity 99%) and 0.3011 g Fe2O3 (purity 99.9%) respectively, and mix them evenly to obtain a mixed powder;

[0056] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the mass ratio of the ball to the material is 35:1.5, and place the ball mill in a planetary ball mill and ball mill it at 600 rpm for 80 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.5Fe2O3-Li2ZrCl6.

[0057] Example 7: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0058] 1. In a glove box, weigh 0.2997 g LiCl (anhydrous, purity 99.9%), 0.8243 g ZrCl4 (anhydrous, purity 99%) and 0.3760 g Fe2O3 (purity 99.9%) respectively, and mix them evenly to obtain a mixed powder;

[0059] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the ball-to-material mass ratio is 35:1.5, place the ball mill in a planetary ball mill and ball mill at 600 rpm for 80 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.66Fe2O3-Li2ZrCl6.

[0060] Example 8: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0061] 1. In a glove box, weigh 0.2662 g of LiCl (anhydrous, purity 99.9%), 0.7322 g of ZrCl4 (anhydrous, purity 99%), and 0.5015 g of Fe2O3 (purity 99.9%), respectively, and mix them evenly to obtain a mixed powder;

[0062] 2. Add the mixed powder obtained in step 1 into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the ball-to-material mass ratio is 35:1.5, and place the ball mill in a planetary ball mill and ball mill it at 600 rpm for 80 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with the chemical formula Fe2O3-Li2ZrCl6.

[0063] Example 9: The preparation method of the low-cost oxide-chloride composite solid electrolyte material of this example is carried out according to the following steps:

[0064] 1. In a glove box, weigh 0.3712 g LiCl (anhydrous, purity 99.9%), 0.1021 g ZrCl4 (anhydrous, purity 99%) and 0.1079 g ZrO2 (purity 99.9%) and mix them evenly to obtain a mixed powder;

[0065] 2. Add the mixed powder into a ball mill made of zirconium oxide (ZrO2) and seal it, wherein the ball-to-material mass ratio is 35:1.5, place the ball mill in a planetary ball mill and ball mill it at 600 rpm for 50 hours to obtain a low-cost oxide-chloride composite solid electrolyte material with a chemical formula of 0.2ZrO2-Li2ZrCl6.

[0066] The price P of the chemical and the purchase quantity Q satisfy P = aQ b The relationship between the two is converted into logP = a + b logQ. Through linear fitting of different purchase quantities and corresponding prices, the price of raw materials and drugs in industrial bulk purchases can be estimated more accurately. Table 1 summarizes the unit prices of raw materials and drugs currently used in the field of halide solid electrolytes (yuan kg -1 ), the drug quotations used are from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0067] Table 1 Unit prices of raw materials and drugs used in the field of halide solid electrolytes

[0068]

[0069]

[0070] By testing the AC impedance spectra of the solid electrolytes obtained in Examples 1 to 9 and Comparative Example 1 and the corresponding thickness of the electrolyte sheet, the ionic conductivity of the corresponding solid electrolyte can be obtained. The AC impedance test is performed using Shanghai Chenhua CHI650D electrochemical workstation. The test frequency range is 2MHz to 10Hz, and the test temperature is 25°C. The test method is as follows: 300mg of electrolyte powder is weighed in a glove box, placed in a test mold of PEEK material with a diameter of d=16mm, a pressure of 20MPa is applied, and maintained for 5min to obtain a cylindrical electrolyte sheet. Stainless steel sheets with a diameter of 15.8mm are placed on both sides of the electrolyte sheet to act as ion blocking electrodes. An AC impedance test is performed, and the impedance value obtained is recorded as R. After the test, the thickness of the tested electrolyte is measured in a glove box in an inert gas environment and recorded as L. Using the formula σ=4L / (πd 2 The test results are shown in Table 2.

[0071] Table 2 Ionic conductivity of solid electrolytes obtained in Examples 1 to 9 and Comparative Example 1

[0072] Sample name Components <![CDATA[Ionic conductivity (mScm -1 )]]> Comparative Example 1 <![CDATA[Li2ZrCl6]]> 0.51 Example 1 <![CDATA[0.2Al2O3-Li2ZrCl6]]> 0.80 Example 2 <![CDATA[0.33Al2O3-Li2ZrCl6]]> 0.82 Example 3 <![CDATA[0.5Al2O3-Li2ZrCl6]]> 0.25 Example 4 <![CDATA[0.2Fe2O3-Li2ZrCl6]]> 1.56 Example 5 <![CDATA[0.33Fe2O3-Li2ZrCl6]]> 1.85 Example 6 <![CDATA[0.5Fe2O3-Li2ZrCl6]]> 1.87 Example 7 <![CDATA[0.66Fe2O3-Li2ZrCl6]]> 2.01 Example 8 <![CDATA[Fe2O3-Li2ZrCl6]]> 1.77 Example 9 <![CDATA[0.2ZrO2-Li2ZrCl6]]> 1.15

[0073] As can be seen from Table 2, the ionic conductivity of Examples 1, 2, and Examples 4 to 9 is significantly improved compared to Comparative Example 1, indicating the effectiveness of the strategy provided by the present invention in improving the lithium ion transport behavior in chloride electrolytes. Among them, Example 7 has the most obvious conductivity improvement effect. The AC impedance spectra corresponding to the ionic conductivity test in the table are as follows Figures 1 to 4 shown.

[0074] Using the raw material drug prices in Table 1, the raw material costs of some halide-based solid electrolytes reported so far were estimated and compared according to the chemical formula and the ratio of the corresponding elements. The results are shown in Table 3.

[0075] Table 3 Raw material costs of some halide-based solid electrolytes

[0076]

[0077]

[0078] Except for Example 2, the ionic conductivity of the halide solid electrolyte species presented in Table 3 is ≥ 2 mS cm -1 , which is a series of electrolytes with good conductivity performance in this field. By comparison, it can be seen that Example 7 provided by the present invention is a halide-based solid electrolyte with the lowest raw material cost that meets this requirement, and its raw material cost is only 279 yuan kg -1 It is worth noting that the chemical formula corresponding to number 14 is Li1.75 ZrCl 4.75 O 0.5 The solid electrolyte has similar ionic conductivity and raw material cost as Example 7. However, the preparation of this electrolyte requires two ball millings and multiple collection and re-proportioning of raw materials / intermediate products. The operating cost is much higher than the one-time ball milling method provided by the present invention, and it is not suitable for promotion of industrial production. The above comparison further illustrates the advanced nature of the strategy provided by the present invention.

[0079] XRD test was performed on the electrolytes of Comparative Example 1, Example 6 and Example 7. The results are as follows: Figure 5 , Figure 6 The peak position in the XRD spectrum of the sample in Comparative Example 1 is consistent with the reported characteristic peak of Li2ZrCl6, and the peak positions of Examples 6 and 7 are consistent with the reported characteristic peak of Li3Zr 3 / 4 OCl4, indicating that the metal oxide enters the Li2ZrCl6 lattice and achieves a partial doping effect. In addition, there are characteristic peaks of Fe2O3 in the XRD spectra of Examples 6 and 7, indicating that Fe2O3 has not completely entered the Li2ZrCl6 lattice and that an independent Fe2O3 phase still exists in the composite electrolyte. The XRD test results show that the addition of metal oxides achieves the dispersion of metal oxide particles in the composite electrolyte and the anion (O 2- ), cation (M m+ )Double doping.

[0080] Example 10: An all-solid-state lithium battery is prepared using the low-cost oxide-chloride composite solid electrolyte material prepared in Example 7. The specific steps are as follows:

[0081] 1. In a glove box in an Ar environment, a Li-In alloy was used as the negative electrode, 30 mg of Li6PS5Cl was used as the interlayer electrolyte, 50 mg of the low-cost oxide-chloride composite solid electrolyte material prepared in Example 7 was used as the main electrolyte, and 8 mg of a composite positive electrode with a mass ratio of LCO:0.66Fe2O3-Li2ZrCl6:Super P=65:30:5 was used as the positive electrode material, and a full-solid-state lithium battery was obtained by pressurizing at 10 MPa in one step.

[0082] All-solid-state lithium batteries were prepared using a PEEK battery test mold. First, a cutting machine was used to cut lithium and indium sheets. The diameter of the lithium sheet was 8 mm and the thickness was 100 μm. The diameter of the indium sheet was 8 mm and the thickness was 150 μm. The cut lithium and indium sheets were stacked in the order of negative electrode current collector, lithium sheet, and indium sheet, with the indium sheet facing the electrolyte side, and manually flattened. Subsequently, 30 mg of Li6PS5Cl powder was placed on the surface of the indium sheet as an interlayer electrolyte and manually smoothed using a steel column. Subsequently, 50 mg of the low-cost oxide-chloride composite solid electrolyte material 0.66Fe2O3-Li2 prepared in Example 7 was placed on the surface of the indium sheet. ZrCl6 was placed on the surface of the separator electrolyte as the main electrolyte and manually smoothed with a steel column; then, 8 mg of the composite positive electrode powder was placed on the surface of the main electrolyte, manually smoothed with a steel column, and then the surface was covered with a positive electrode current collector; finally, a PEEK mold was assembled and pressurized to 10 MPa to obtain an all-solid-state battery; wherein the composite positive electrode powder was mixed with lithium cobalt oxide (LiCoO2, LCO), the low-cost oxide-chloride composite solid electrolyte material 0.66Fe2O3-Li2ZrCl6 prepared in Example 7 and super carbon black (Super P) in a mass ratio of 65:30:5; the structural schematic diagram of the all-solid-state battery is shown in FIG. Figure 7 shown.

[0083] After the all-solid-state lithium battery was prepared and left for 8 hours, the charge and discharge test was performed on the whole battery. The test conditions were: 0.05C rate (1C = 140mAg -1 ) The full battery was activated for 3 cycles, and the charge cut-off voltage was set to 3.68V (for Li + / Li electrode potential is 4.3V), the cut-off current in the constant current stage is set to 0.01mA, and the discharge cut-off voltage is set to 2.48V (for Li + / Li electrode potential was 3.1 V), and then the cyclic charge and discharge tests were carried out at 0.5C with the same cut-off voltage and cut-off current.

[0084] Figure 8 This is a coulombic efficiency-capacity diagram of the constant current-constant voltage charge / constant current discharge test of the all-solid-state lithium battery prepared in Example 10, Figures 9 to 13 The charge and discharge curves of the all-solid-state lithium battery prepared in Example 10 at different cycle numbers. The charge and discharge test results show that the assembled all-solid-state lithium battery has excellent stability. In 50 cycles, the discharge capacity remains at 120 mAh g -1 The coulombic efficiency is stable at around 100%, and no obvious capacity decay is observed. The charge and discharge curves of different cycles have a high degree of overlap, and the first cycle charge and discharge efficiency remains above 85%, which is consistent with the theoretical performance of the LCO positive electrode.

[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A low-cost oxide-chloride composite solid electrolyte material, characterized in that: The chemical formula of the composite solid electrolyte material is xMO m / 2 -Li2ZrCl6, where 0 < x < 2, M is the metal element in the oxide, and m is the valence of the metal element M; M is one or more of Al, Fe, La, Ce, Sm, Nd, Ti, Zn, Cu, Mg, Zr, Cr, Mn, V, Ca, and Sn.

2. A method for preparing a low-cost oxide-chloride composite solid electrolyte material according to claim 1, characterized in that: The method proceeds as follows:

1. According to the stoichiometric ratio of xMO m / 2 -Li2ZrCl6, mix the raw materials LiCl, ZrCl4 and MO m / 2 uniformly to obtain a mixed powder; where in xMO m / 2 -Li2ZrCl6, 0 < x < 2, M is the metal element in the oxide, and m is the valence of the metal element M; M is one or more of Al, Fe, La, Ce, Sm, Nd, Ti, Zn, Cu, Mg, Zr, Cr, Mn, V, Ca and Sn; 2. The mixed powder described in step 1 is ball-milled for 16 to 500 hours at a ball-to-material mass ratio of (5 to 40):(1 to 2) and a ball-milling speed of 400 to 700 rpm to obtain a low-cost oxide-chloride composite solid electrolyte material.

3. The method for preparing a low-cost oxide-chloride composite solid electrolyte material according to claim 2, characterized in that: The ball milling process described in step 2 is completed under inert gas protection conditions.

4. The method for preparing a low-cost oxide-chloride composite solid electrolyte material according to claim 2 or 3, characterized in that: The ball milling process described in step 2 is carried out in an argon (Ar) environment with a water content and an oxygen content of <0.01 ppm.

5. The use of a low-cost oxide-chloride composite solid electrolyte material according to claim 1, characterized in that: The application is to use low-cost oxide-chloride composite solid electrolyte materials as electrolyte materials for lithium-ion batteries.

6. The use of a low-cost oxide-chloride composite solid electrolyte material according to claim 5, characterized in that: It is to use low-cost oxide-chloride composite solid electrolyte materials in all-solid-state lithium batteries.

7. The use of a low-cost oxide-chloride composite solid electrolyte material according to claim 6, characterized in that: In the all-solid-state lithium battery, the solid electrolyte utilizes a low-cost oxide-chloride composite solid electrolyte material as the main electrolyte; the positive electrode is formed by mixing an active substance, a low-cost oxide-chloride composite solid electrolyte material and a conductive agent in a mass ratio of (60-70):(20-30):(0-20); the active substance is lithium cobalt oxide and / or a nickel-cobalt-manganese ternary lithium positive electrode material; the conductive agent is one or a combination of carbon nanotubes, vapor-grown carbon fibers and super carbon black.

8. The use of a low-cost oxide-chloride composite solid electrolyte material according to claim 7, characterized in that: The interlayer electrolyte of all-solid-state lithium battery is Li3PS4, Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Cl、Li 10 GeP2S 12 and Li7P3S 11 One or a combination of several of them.

9. The use of a low-cost oxide-chloride composite solid electrolyte material according to claim 7, characterized in that: The negative electrode of the all-solid-state lithium battery is a lithium-indium alloy.

10. The use of a low-cost oxide-chloride composite solid electrolyte material according to claim 8, characterized in that: The mass ratio of the main electrolyte to the separator electrolyte of the all-solid-state lithium battery is (1-10):3.

Citation Information

Patent Citations

  • Composite solid electrolyte film and preparation method and application thereof

    CN115458801A

  • Oxygen-containing chloride solid electrolyte and preparation method and application thereof

    CN115842157A

  • All-solid-state lithium ion battery

    CN117154202A

  • Oxygen chloride-based solid electrolyte material and solid-state battery

    CN119361807A

  • Solid electrolyte material, preparation method, electrode, and lithium ion battery

    WO2024174452A1